Construction of Bi4Ti3O12@ZnIn2S4 heterostructures: Photocatalytic performance and chemical speciation investigation - Nikolaos Karamoschos; Andreas Katsamitros; Ioannis Konstantinou; Dimitrios Tasis (Next Materials)
In this study, 2D/3D Bi4Ti3O12@ZnIn2S4 hybrid photocatalytic systems were prepared by a facile two-step hydrothermal process, whereas their morphology, chemical speciation and optical properties were investigated in detail. Information from surface analysis demonstrated the co-existence of Bi3-x suboxide species with unsaturated coordination within Bi4Ti3O12 lattice. Vibrational characterization revealed a submicron-scale homogeneity in the grains of ZnIn2S4-enriched hybrid. Besides the involved semiconducting components, additional Raman peaks were recorded, which were attributed to Bi4-xMxTi3O12 species (M: Zn and/or In). The absorbance of such Bi4Ti3O12@ZnIn2S4 hybrids spanned from the ultraviolet up to the visible/near-infrared limit. The optimized hybrid (containing 16 wt% of Bi4Ti3O12) was able to photodegrade 97.5 % of an azo-dye within 60 min irradiation under visible wavelengths. Scavenging experiments revealed a lack of selectivity for a specific oxidation path. Transients, such as holes, hydroxy radicals and singlet oxygen acted complementary towards the oxidative degradation of azo-dye.